Implementation Plan in Response to Board-Endorsed Recommendations Arising from the IEO Evaluation of IMF Interactions with Member Countries. (Policy Papers; Policy Paper, 2010)
This supplement reports on progress on various issues outlined in the staff's Implementation Plan since its initial issuance on June 1, 2010. Many of the steps included in the Implementation Plan, particularly proposals in the Mandate papers still under consideration last June, have been taken forward. These initiatives are aimed at better integration of bilateral and multilateral surveillance, sharpening analysis of financial sector issues and macro-financial linkages, and better tailoring of the Fund's lending toolkit to members' needs and circumstances. Many further initiatives are included in the latest Work Program, which was discussed by the Board on November 22, 2010.